2015
DOI: 10.1371/journal.pone.0122475
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Basis of Risky Choice with Affective Outcomes

Abstract: Both normative and many descriptive theories of decision making under risk are based on the notion that outcomes are weighted by their probability, with subsequent maximization of the (subjective) expected outcome. Numerous investigations from psychology, economics, and neuroscience have produced evidence consistent with this notion. However, this research has typically investigated choices involving relatively affect-poor, monetary outcomes. We compared choice in relatively affect-poor, monetary lottery probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 56 publications
4
32
0
1
Order By: Relevance
“…Differences in decision strategies and cognitive processes between choices with medical and monetary prospects have been systematically examined in several studies (Lejarraga et al, 2016;Pachur et al, 2014;Pachur & Galesic, 2013;Suter et al, 2016Suter et al, , 2015. These studies suggest that in the medical domain compared with the monetary domain, people focus more on avoiding the worst outcome, largely disregarding the probability of the outcomes.…”
Section: Discrepancies Between Medical and Monetary Choicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in decision strategies and cognitive processes between choices with medical and monetary prospects have been systematically examined in several studies (Lejarraga et al, 2016;Pachur et al, 2014;Pachur & Galesic, 2013;Suter et al, 2016Suter et al, , 2015. These studies suggest that in the medical domain compared with the monetary domain, people focus more on avoiding the worst outcome, largely disregarding the probability of the outcomes.…”
Section: Discrepancies Between Medical and Monetary Choicesmentioning
confidence: 99%
“…When faced with medical rather than monetary prospects, however, people seem to rely on a substantially different mechanism. Specifically, people often seem to neglect probability information and to rely on simpler, heuristic decision strategies (Lejarraga, Pachur, Frey, & Hertwig, ; Pachur & Galesic, ; Pachur, Hertwig, & Wolkewitz, ; Suter, Pachur, & Hertwig, ; Suter, Pachur, Hertwig, Endestad, & Biele, ).…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation for the differences in decision patterns and risk preference across domains may come from the affect involved in healthcare-related decisions [28]. Several behavioral studies have identified differences in decision making between affect-rich and affect-poor tasks [2933].…”
Section: Discussionmentioning
confidence: 99%
“…This distinction is important because multiple models of decision making under risk share the common notion that outcomes are weighted by their probability, maximizing the expected outcome. However, when faced with emotion or affect-charged decisions, evidence suggests that people systematically choose the optimal option less often [28]. And others have suggested that the impact of probability information may be attenuated in affect-rich choices [34].…”
Section: Discussionmentioning
confidence: 99%
“…There it has had vast implications, as citation scores show. It is well known that preferences for health outcomes may differ from decisions for financial outcomes (even at a neurological level, see Suter, Pachur, Hertwig, Endestad, & Biele, ). Such differences have been observed for time preferences (e.g., Attema, Bleichrodt, L'Haridon, Peretti‐Watel, & Seror, ; Chapman, ), ambiguity preferences (e.g., Curley, Eraker, & Yates, ), and, most relevant to our purposes, risk preferences (e.g., Suter, Pachur, & Hertwig, ; Weber, Blais, & Betz, ).…”
Section: Introductionmentioning
confidence: 99%